Audit Energi Pada Gedung Fakultas Ilmu Sosial Dan Ilmu Politik (FISIP) Universitas Teknologi Sumbawa - rifqi sahrul ramdani; Indra Darmawan; Masyitah Aulia (Program Studi Teknik Elektro, 2023)
The level of electricity consumption must be balanced and efficient [1]. However, not all sectors are able to meet the predetermined efficiency level. This is due to several factors. Among these factors is the use of inappropriate lighting and air conditioning systems [2]. The Sumbawa University of Technology (UTS) Faculty of Social and Political Sciences (FISIP) building as a consumer of electrical energy, it is necessary to analyze energy saving opportunities. The purpose of this study was to analyze opportunities for energy saving through a brief energy audit guided by SNI 6196: 2011. The method used in this study was a mixed method research. The results of the study obtained IKE in the kWh of the FISIP building of 14.739 kWh/m2/year. In air-conditioned rooms, the average IKE value was 12.07 kWh/m2/month, for non-AC rooms, the average IKE value was 0.5114 kWh/m2/month. In general, the use of electrical energy is classified as very efficient.